Genre and the invention of the writer : reconsidering the place of invention in composition - Bawarshi, Anis S. (Utah State University Press, 2003)
In a focused and compelling discussion, Anis Bawarshi looks to genre theory for what it can contribute to a refined understanding of invention. In describing what he calls "the genre function," he explores what is at stake for the study and teaching of writing to imagine invention as a way that writers locate themselves, via genres, within various positions and activities. He argues, in fact, that invention is a process in which writers are acted upon by genres as much as they act themselves. Such an approach naturally requires the composition scholar to re-place invention from the w